Staphylococcal Scalded Skin Syndrome in Healthy Infant - Anggia Perdana Harmen (Majalah Kedokteran Andalas, 2022)
Staphylococcal scalded skin syndrome (SSSS) describes a spectrum of superficial blistering skin disorders caused by the exfoliative toxins of Staphylococcus aureus that originates from a focus of infection that may be a purulent conjunctivitis, otitis media, or occult nasopharyngeal infection. It usually begins with fever, irritability, and a generalized, paint, orange-red, macular erythema with cutaneous tenderness, and the rash progress from scarlatiniform to a blistering eruption in 24 to 48 hours. A diagnosis must distinguish SSSS from other skin diseases, such as toxic epidermal necrolysis, epidermolysis bullosa, bullous erythema multiforme, Streptococcal impetigo or listeriosis and thermal or chemical burns, all of which can manifest with similar symptoms. The prognosis of SSSS in children who are appropriately treated is good, with a mortality of less than 5%. A case was a three moths old boy hospitalized in Pediatric ward M. Djamil hospital with chief complain redness and peeling of the skin since 2 days before hospitalized. Culture of the skin, eyes and nose was Staphylococcus aureus, and patients was given ampicillin and gentamycin for seven days.